2011
DOI: 10.1016/s0917-2394(11)70238-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of palatal rugae shape in two samples of Egyptian and Saudi children

Abstract: This study was performed to investigate differences in the shape of the individual palatal rugae in two population samples of Arabian children from Egypt and Saudi Arabia, and develop discriminant function to identify the populations based on rugae shape. A total of 152 stone casts (80 from Egyptian and 72 from Saudi children), equally distributed between genders aged 6-8 years were examined for rugae shape (straight, wavy, curved, circular, unification and cross-link) and their incidence was recorded. Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
6
13
2
Order By: Relevance
“…These findings are inconsistent with Abdellatif et al, (2011) who reported that diverging rugae were significantly higher in number among Saudi populations while converging rugae were significantly higher among Egyptians. Saudi populations possessed (27) divergent compared to (8) convergent ones while Egyptians had (15) and (23) divergent and convergent rugae respectively.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…These findings are inconsistent with Abdellatif et al, (2011) who reported that diverging rugae were significantly higher in number among Saudi populations while converging rugae were significantly higher among Egyptians. Saudi populations possessed (27) divergent compared to (8) convergent ones while Egyptians had (15) and (23) divergent and convergent rugae respectively.…”
Section: Discussioncontrasting
confidence: 96%
“…Concerning the females, the Egyptians had significantly greater line shaped rugae while the Malaysians had significantly greater sinous shape rugae than the Egyptians. The results of this current study partially agree with Abdellatif et al (2011) who observed that both sexes of Egyptian and Saudi volunteers had insignificant differences regarding rugae shape. Surprisingly, they noted that Egyptians had significantly higher curve shaped rugae than Saudis who showed significantly higher sinous shaped rugae.…”
Section: Discussionsupporting
confidence: 92%
“…This finding indicates the need for describing/identifying other shapes and conducting a larger scale study. The findings of this study confirm previous findings with respect to Egyptian and Saudi children [1], Saudi adults [9], and Indians [13,21,26] where wavy and curved rugae are the most common shapes followed by straight rugae. The results are also consistent with those reported for Australian Aborigines and Caucasian populations as they, too, are found to have a higher prevalence of wavy-and curved-shaped rugae [14].…”
Section: Discussionsupporting
confidence: 91%
“…That is, converging shapes are found to be sexually dimorphic and higher in females [9]. However, shapes did not show any sexual dimorphism among Jordanians [19], Rwandans [11], Egyptians or Saudi children [1]. This may be attributable to the classification used regarding the shapes used in the study, as it indicates that non-specific rugae are sexually dimorphic while converging unified rugae differ significantly between males and females in Sudanese Nubians and Saudi adults [9].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that presence of the unification rugae pattern in the Saudi population with the diverging form is more prevalent than the converging form. On the contrary to the results reported by (Abdellatif et al, 2011) who compared unification forms of palatal rugae between the Egyptian and Saudi children and stated that, converging rugae were more frequent in Egyptians, while diverging rugae were more frequent in Saudi children.…”
Section: Discussioncontrasting
confidence: 89%